Training load quantification in italian professional football team third division (serie C 2021-2022); within and between microcycle comparisons - Izzo, R.; Cejudo, A.; Giovannelli, M. (Journal of Physical Education and Sport, 2022)
The aim of this study is analyzed training load quantification in Italian Professional football club (Serie C 2021-2022), during a week with 1 match. Twenty-five (n=25) élite football players participated in this study (age 24.1±1.4; body weight 79.8±1.7; height 182.9±0.6; fat mass 12.1±3.5), without goalkeepers. Every player has been analyzed with a K-AI live device 50Hz (K-Sport Universal STATS, Italy) in 299 training and 39 official matches for regular seasons. The game week analyzed are 26 with 1 match on Saturday or Sunday. Data show that distance covered in sprint (D_S7 > 25km/h) is different respect to MD (match day) and MD-2; but the same in every day (MD+2; MD+3; MD-3) in all training, due probably to the lack of specific physical training during "strong day" of week (MD+2; MD+3; MD-3). In MD-2, gradually decreases training load, because is near to match day. Insted for distance covered at high intensity (D_S5 >20Km/h), is the same in MD+3 and MD-3 and different in other training and MD. This confirm there haven`t been change in training load at high intensity during MD+3 and MD-3, as indicated by physiology of soccer. Weekly training load is completely flat, without undulatory trend: every day the same result in sprint distance and acceleration at very high intensity (MD+2; MD+3 ,MD-3). Infact during season, last 6-7 game week, acceleration and sprint are completely decreased: the concurrent decrease in the overall parameters may suggest a periodisation strategy that is able to compensate for the increased load derived from high-speed distances.